Management of hereditary gingival fibromatosis: A 2 years follow-up case report - Amitandra Kumar Tripathi; Gopal Dete; Charanjeet Singh Saimbi; Vivek Kumar (Wolters Kluwer Medknow Publications, 2015)
Hereditary gingival fibromatosis (HGF) is a rare hereditary condition characterized by slow, progressive, nonhemorrhagic, fibrous enlargement of gingiva due to increase in sub-mucosal connective tissue component. This paper presents a case report of an 18-year-old female suffering from HGF with positive family history. Her 42-year-old mother also have enlargement of the gums. After through clinical examination of both the patients, routine blood investigation was advised. All the investigations were within normal physiological limits of both the patients. Surgical excision of enlarged gingival tissue was planned after meticulous scaling and root planing. Patients were recalled 1 week after surgery. Postoperative healing were good and desired crown lengthening was achieved with significant improvement in speech and masticatory problems in both the patients. There was no recurrence of the disease even after 2 years follow-up.